Rigorous derivation of dark energy and inflation as geometry effects in Covariant Canonical Gauge Gravity. Issue 1 (26th January 2021) - Vasak, David; Kirsch, Johannes; Struckmeier, Jürgen
Abstract : The cosmological implications of the Covariant Canonical Gauge Theory of Gravity (CCGG) are investigated. CCGG is a Palatini theory derived from first principles using the canonical transformation formalism in the covariant Hamiltonian formulation. The Einstein‐Hilbert theory is thereby extended by a quadratic Riemann‐Cartan term in the Lagrangian. Moreover, the requirement of covariant conservation of the stress‐energy tensor leads to necessary presence of torsion. In the Friedman universe that promotes the cosmological constant to a time‐dependent function, and gives rise to a geometrical correction with the EOS of dark radiation. The resulting cosmology, compatible with the ΛCDM parameter set, encompasses bounce and bang scenarios with graceful exits into the late dark energy era. Testing those scenarios against low‐ z observations shows that CCGG is a viable theory.